Business-to-business marketing management strategies, cases, and solutions - Glynn, Mark S.; Woodside, Arch G. (Advances in business marketing & purchasing, 2012)
This book provides knowledge and skill-building training exercises in managing marketing decisions in business-to-business (B2B) contexts. The topic coverage is broad and deep. The intent is for the book to help answer four questions: (1) what questions should executives ask when crafting and implementing effective strategies in B2B contexts; (2) what tentative answers may be useful for executives to consider to these questions; (3) what skills in crafting strategies and decisions are necessary for executives to excel in for achieving effective outcomes consistently; and how should the B2B go about acquiring these skills?.